Visual cognition and experience mediate the relation between age and decision making in youth volleyball players - De Waele, S.; Van Bostraeten, S.; Lenoir, M.; Deconinck, F.; Bennett, S. J. (Optometry and Vision Science, 2021)
Significance: Experts in different sports show superior decision making skills compared to novices, but little is known about its development in youth players. This study shows that the age-related improvements in visual cognition and accumulation of sport-specific experience explain a considerable amount of the development in decision making in volleyball. Purpose: The aim of this study was to investigate the mediating effects of visual cognition and volleyball experience on the relationship between age and decision making in youth volleyball players. Methods: 171 Female volleyball players aged 6-17 years old performed a sport-specific, video-based test of decision making, as well as 4 different visual cognition tests. Using structural equation modeling, we examined if volleyball experience and a latent variable constructed from the four tests of visual cognition act as parallel mediators in the association between age and decision making. Results: The parallel multiple mediation model for the association between age and decision making was supported in youth volleyball players. Moreover, significant indirect effects and a non-significant direct effect indicated that visual cognition and experience fully mediated the relation between age and decision making, and together explain 38% of the variance in decision making performance. The effects of both mediators were not significantly different and there was no residual correlation between experience and visual cognition, which indicates that these mediators are unrelated to each other. Conclusions: Our findings demonstrate that visual cognition and volleyball experience mediate the relation between age and decision making independently, which indicates that they each influence different parts of the decision making process. These results highlight the importance of the development of perceptual-cognitive skill in young players and future research should further investigate the development of these skills as well as their underlying factors in different kinds of sports.